Quality assurance interventions in blended learning design: A systematic review of the literature - Benson, Helen; Williams, Kylie A; Heggart, Keith (Australasian Journal of Educational Technology, 2024)
The COVID-19 pandemic has accelerated the shift in higher education towards blended and online learning, prompting a need for robust quality assurance interventions. Blended learning, a combination of face-to-face and online experiences, offers flexibility and individualised learning paths, but its quality varies across institutions. Quality assurance interventions play a crucial role in monitoring and enhancing the effectiveness of blended learning programs. This systematic literature review examined existing literature on quality assurance interventions in blended learning within higher education. The review highlights the importance of evaluating the impact of these interventions on student performance and the educational landscape. It also emphasises the need for evidence-based frameworks for benchmarking and assessment. The review identifies four key intervention approaches: professional development courses, communities of practice and mentoring, audit frameworks and learning design support. Each approach has its strengths and can contribute to improving the quality of blended learning. Future research should focus on multifaceted interventions that combine these approaches to enhance the skills of academics and elevate the standard of blended learning across institutions. Implications for practice or policy: This review can guide higher education institutions in implementing quality assurance activities to enhance their online and blended learning offerings. Evidence-based approaches that institutions can adopt include professional development courses, communities of practice and learning design support interventions.